Cystatin C as an indicator of renal damage in pre-eclampsia - Hellen Cássia Dos Santos Gomes; Antônio Carlos Vieira Cabral; Silvia Passos Andrade; Henrique Vítor Leite; Patrícia Gonçalves Teixeira; Paula Peixoto Campos; Jaqueline Amorim Arantes Gomes (Taylor & Francis Group, 2020)
Objective To assess the predictive abilities of serum and urinary cystatin C levels for glomerular lesions in pregnant women with pre-eclampsia. Methods In this study, kidney function markers were compared between38 pregnant women with pre-eclampsia and 22 healthy pregnant women. Results The serum and urine levels of cystatin C and urea were significantly higher in the pre-eclampsia group than in the control group. Receiver operating characteristic curve analysis demonstrated that the serum cystatin C level (91.7%) had a superior diagnostic accuracy for pre-eclampsia than the other markers. Conclusion Serum cystatin C level maybe a significant marker of pre-eclampsia.